ANALISIS KARAKTERISTIK SOSIAL EKONOMI TUKANG OJEK DI KELURAHAN KEBUN SIRIH - Yaref Asso; Longginus Gelatan (JIEKA: Jurnal Integrasi Ekonomi, Keuangan, dan Akuntansi, 2026)
This study aims to identify the socio-economic characteristics of motorcycle taxi drivers in the Kebun Sirih neighbourhood. Research Methodology. The research methodology employed descriptive statistics. In this study, the data collection technique used was a questionnaire; the sample size comprised 51 respondents. The results of this study indicate the socio-economic characteristics of motorcycle taxi drivers in the Kebun Sirih sub-district.